A Pedagogia da alternância na visão dos egressos da EFA de Porto Nacional - TO: a possibilidade de uma formação integral - CAVALCANTE, Nilton Vale (Universidade Federal do Pará, 2011)
Submitted by Albirene Sousa (albirene@ufpa.br) on 2011-04-07T14:27:34Z No. of bitstreams: 2 CAVALCANTE, Nilton Vale PPGEducação.pdf: 2754366 bytes, checksum: 673f8f248e39068f652142737ea3e0c5 (MD5) license_rdf: 22876 bytes, checksum: 0a4e855daae7a181424315bc63e71991 (MD5) === Made available in DSpace on 2011-04-07T14:27:34Z (GMT). No. of bitstreams: 2 CAVALCANTE, Nilton Vale PPGEducação.pdf: 2754366 bytes, checksum: 673f8f248e39068f652142737ea3e0c5 (MD5) license_rdf: 22876 bytes, checksum: 0a4e855daae7a181424315bc63e71991 (MD5) Previous issue date: 2009 === In this study it was analized how the Integral Formation of young people, one of the main purposes of the network Centros Familiares de Formação por Alternância (Familiar Centers of Alternation Formation), has been happening at Escola Família Agrícola (Agricultural Family School), in the city of Porto Nacional, and how occurs the participation of its egresses in the different aspects of social life. The research is based on the qualitative approach with dialectical perpective, that here has the form of case study. We combined the use of bibliographic research with other methodological procedures, such as documentary research from which it was analysed, among other situations, the Political and Pedagogical Project of the Agricultural Family School, reports, Education Laws and opinions. We still applied semistructuralized type interviews, with 14 chosen egresses, after applying a questionnaire answered by 32 of the 103 total students that had finished the High School and Professional Education at the Agricultural Family School, until the year of 2006. At the main documents of that School, it was clear the assumption that it can contribute with the Integral Formation of its young people, by trainning them for the citizenship and building a culture of participation. The Country Education, in Brazil history, is a concrete example of indifference and refuse of a right by the Brazilian State, from what is responsability of public policies to include the country population. It is in this empty of denying people their rigths, not only done by the State, but also and mainly by the powerful social elites of Brazil, that it is born, within the civil society of Porto Nacional, the Agricultural Family School, helping country people of that region. The Agricultural Family School was created by COMSAÚDE, a nongovernmental organization, and it came from debates with country comunities of Porto Nacional and local Social Movements. One of the purposes to the creation of the School is to help people that live at the country region, giving them a quality education and reflecting the particularities of that population, working with the Familiar Agriculture. The research concluded that the Scool advances by working knowledge from reading people reality, in the light of other knowledges and possibilities and that the School contributes to form citizens at the Integral Formation of its young people. === Neste estudo analisamos como a Formação Integral dos Jovens, um dos pilares fins da rede de Centros Familiares de Formação por Alternância (CEFFA), vem se materializando na Escola Família Agrícola (EFA) de Porto Nacional e como se dá a participação de seus egressos nos diversos aspectos da vida social. A pesquisa baseia-se na abordagem qualitativa com perspectiva dialética, que aqui assume a forma de estudo de caso. Combinamos o uso da pesquisa bibliográfica com outros procedimentos metodológicos como a pesquisa documental, por meio da qual analisamos, entre outros, o Projeto Político e Pedagógico da EFA, relatórios, Leis da Educação e Pareceres. Realizamos, ainda, entrevistas do tipo semiestruturada com 14 egressos escolhidos, após a aplicação de um questionário respondido por 32 dos 103 estudantes que concluíram o Ensino Médio e o Ensino Profissionalizante na EFA, até o ano de 2006. Nos principais documentos da EFA de Porto Nacional, fica expressa a suposição de que a Escola pode contribuir para a Formação Integral de seus jovens, formando-os para a cidadania e construindo uma cultura de participação. A Educação do Campo, na história do Brasil, é um exemplo bem claro do descaso e da negação desse direito por parte do Estado brasileiro, no que diz respeito às políticas públicas para atender os povos do campo. É nesse vácuo da negação do direito, não só pelo próprio Estado, mas também, e principalmente, pelas classes dominantes de nosso país que nasce, no seio da sociedade civil de Porto Nacional, a Escola Família Agrícola, atendendo os jovens do campo daquela região. A EFA foi criada pela COMSAÚDE, uma instituição não-governamental, a partir de debates com as comunidades do campo de Porto Nacional e os Movimentos Sociais locais. Um dos objetivos da criação da Escola era o de atender os sujeitos do campo com uma Educação de qualidade e voltada para as especifidades dessa população, dando ênfase à Agricultura Familiar. A pesquisa concluiu que a Escola avança na medida em que trabalha o conhecimento a partir da leitura da realidade, à luz de outros conhecimentos e possibilidades no seu meio e que ela vem contribuindo para a Formação Integral e cidadã de seus jovens.